Interrogating nego-feminism in six Nigerian novels - Alkali, Muhammad (2013)
The study explores the syndrome of domestic subjugation closely through a progression of already established three generations in Nigerian literary life. While the first generation of writers subjugated women, the efforts of feminist novelists in second generation have arisen, in consequence, to free woman’s trampled life, and yet the challenges persist. The study argues, the oppositional feminist approach evident in such novels may have also been overdone and therefore, not adequate in charting a relieving course, hence, fixation of Nigerian woman’s plight from the historical disadvantage relative to patriarchal novels. There is the need for an alternative paradigm, Nego-feminism, in which to assess and provide healthier relationship models for those in, or wishing to, understand conventional, heterosexual, and particularly Nigerian male-female relationships. The study proposes, therefore, the exploit of the emergent third generation novels through negotiation-feminism as framework for adequate reconciliatory effort of lively-partnership. It recommends further that once teachers and identifiable new Nigerian writers are separately put together in workshops and seminars for mental shift towards the framework, chances are that the Nigerian feminist world would be happier for sexual co-existence.